CICURUG CULINARY SMES STRATEGIES IN MAINTAINING BUSINESS IN THE DIGITALIZATION ERA - Nurrahman, Mita (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in strengthening economic structures, especially in developing countries like Indonesia. Despite their significant contribution to employment and GDP, MSMEs still face various barriers such as limited access to digital technology, financial constraints, and insufficient managerial capacity. These challenges become even more critical in the digital era, where technology adoption is key to maintaining business sustainability and competitiveness. This study aims to explore the strategies employed by culinary MSMEs in Cicurug District, Sukabumi Regency, in adapting to digital transformation. Using a qualitative descriptive approach with a case study strategy, data were collected through semi-structured interviews, field observations, and documentation. The results indicate that most culinary MSMEs in Cicurug have begun adopting digital platforms such as social media, food delivery apps, and e-commerce for marketing, customer engagement, and distribution. However, several issues persist, including limited digital literacy, infrastructure barriers, and the need for continuous innovation to meet rapidly changing consumer preferences. The findings highlight the importance of enhancing human resource capacity, promoting collaboration between government and private digital platforms, and fostering local-based digital training. This research contributes to understanding how MSMEs navigate digital challenges and offers practical insights for policy formulation and future development programs. Further research is needed to evaluate the long-term impact of digital strategies on business resilience and scalability in other rural regions.